Comparison of the effectiveness of single- and multiple-sessions disinfection protocols against endotoxins in root canal infections: systematic review and meta-analysis - Nascimento, Gustavo G.; Rabello, Diego G. D. [UNESP]; Corazza, Bruna J. M. [UNESP]; Gomes, Ana P. M. [UNESP]; Silva, Eduardo G. [UNESP]; Martinho, Frederico C. (Nature Research, 2021)
This systematic review (SR) addressed the following common clinical question: What is more effective in reducing or eliminating endotoxin in endodontic infections-single or multiple-session treatments using calcium hydroxide medications? Literature searches of Medline/PubMed, Embase, Cochrane Library, Scielo, Science Direct, Web of Knowledge, Scopus, and Google Scholar databases. Two reviewers independently assessed the eligibility for inclusion, extracted data, and evaluated the quality of the studies using the risk of bias tools. Electronic searches resulted in 358 articles, of which 32 studies were included for full-text assessment, and nine were included in this review. Meta-analysis pooling all the nine studies revealed lower levels of endotoxin for multiple-session treatment (P<0.001). The sub-group analysis indicated no difference between single-session and 7 days of Ca(OH)(2) medication (SMD - 0.32; P=0.22). However, 14-days (I-2=80.5%, P<0.001) and 30-days (I-2=78.9%, P<0.01) of Ca(OH)(2) medication was more effective than single-session treatment (both, p<0.001). Overall, Overall, this SR provides evidence to support that multiple-session disinfection protocols with the placement of Ca(OH)(2) medications are more effective in reducing the levels of endotoxin from root canal infections compared to single-session when applied for 14 and 30 days.